XML Gateway for Heterogeneous Distributed Database Management Systems - Aslam Parvez Memon; Muhammad Nadeem (JISR Management and Social Sciences & Economics, 2004)
Conventional standalone application development paradigm is being transformed into multi-layered application development process. The main reason of transformation is the execution environment— particularly internetworking. The above mentioned transformation requires major changes in the platforms i.e. Hardware, Software, application development tools, and database management systems. This study especially focuses on the data related issues of applications, running on distributed platforms. The key attributes of distributed applications’ data include Autonomy, Distribution and Heterogeneity. Autonomy of DBMS can be defined as a degree to which a database management system can operate independently, which can be implemented at design, communication and execution level. Distribution deals with data distribution on diverse network platforms. Database Management System components can vary in Data Model, Data Structure, Query Languages, Data Manipulation, Schema, Operating System, Hardware, Location. The Databases that differ in these are termed as Heterogeneous Databases. Today’s applications often need integration of databases deployed on variety of platforms and possibly supporting different data models and data structures. It seems very difficult to implement the above stated attributes in different database management systems provided by various vendors. In order to integrate the information from heterogeneous data sources, it is necessary to form a gateway or mediator architecture. XML (eXtensible Markup Language) is a portable data definition and transportation language. One of the major applications of XML is to provide the mediation between two or more heterogeneous databases. This study aims at designing a prototype for accessing heterogeneous data sources using XML standard. Additionally the comparative study of Databases and XML has been carried out to present XML as potential candidate for data modeling and data definition requirements of any application. Furthermore an interactive data cleaning, analysis and transformation model has been added to integrate the diverse data and perform variety of data cleaning operations.